2015
DOI: 10.1002/ange.201505648
|View full text |Cite
|
Sign up to set email alerts
|

Säurevermittelte Bildung von Radikalen oder Baeyer‐Villiger‐Oxidation, ausgehend von Criegee‐Addukten

Abstract: In dieser Zuschrift ist ein Fehler aufgetreten, da die berechneten Bindungsdissozia-tionsenergien (BDE) fürVerbindungen 15 a und 15 b verwechselt wurden. Die korrigierte Abbildung 1mit den korrekten Werten ist unten gezeigt. Die Diskussion im Manuskript und alle Schlussfolgerungen werden dadurch nicht beeinträchtigt. In gleicher Weise sind in Tabelle S3 der Hintergrundinformationen die BDE-Werte von Verbindungen 15 a und 15 b vertauscht worden. Zusätzlich müssen die Enthalpiewerte einiger Strukturen in Tabelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Typically,t he addition reactions of radicals to double bonds are described by as tate correlation diagramt hat helps provide an understanding of the factors that influence the reactions. [9b] In such ap otential energy profile, the reactant ground-state configuration (RC + styrene in as inglet state), the excited reactant configuration (RC + styrene in at riplet state), and two polar charge-transfer configurations (CTCs), DE CT1 and DE CT2 ,E quations (1) and (2) and Figure 2a re considered. The former, DE CT1 , accountsf or the transfer of an electron onto the styrene,a nd the latter, DE CT2 ,a ccounts for the transfer of an electron onto the radical.…”
Section: All the Calculated Rse Values Presented Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically,t he addition reactions of radicals to double bonds are described by as tate correlation diagramt hat helps provide an understanding of the factors that influence the reactions. [9b] In such ap otential energy profile, the reactant ground-state configuration (RC + styrene in as inglet state), the excited reactant configuration (RC + styrene in at riplet state), and two polar charge-transfer configurations (CTCs), DE CT1 and DE CT2 ,E quations (1) and (2) and Figure 2a re considered. The former, DE CT1 , accountsf or the transfer of an electron onto the styrene,a nd the latter, DE CT2 ,a ccounts for the transfer of an electron onto the radical.…”
Section: All the Calculated Rse Values Presented Inmentioning
confidence: 99%
“…[1] They can easily be generated by the acid-catalyzedc ondensation of simple ketones such as acetonew ith tert-butyl hydroperoxide (tBuOOH), and the resulting alkenyl peroxide 1 decomposes into tert-butyloxyl and the acetonyl (2-oxopropan-1yl) radical 2 (Scheme 1a). [2] This method constitutes as imple means of generating a-keto radicals from nonactivated ketones. [3] Both radicals can be utilized in addition reactions to olefins, [4] for example, to synthesize the g-peroxy ketone 3.…”
Section: Introductionmentioning
confidence: 99%
“…The radicalp olymerizationo fm ethyl methacrylatec ould be initiated by sulfuric acid, ketonesa nd tBuOOH at 40 8C, which is well below the T 10h t1=2 for tBuOOHa lone (see Scheme 5above). [32] The mechanism for this initiation method was later suggested to involvea lkenyl peroxide formation as shown in Scheme 7, [33] and the method was also appliedf or RAFT polymerization of variousm onomersa t2 5 8C, using p-toluenesulfonic acid. [34] It was shown that the initiation proceeded faster when geminal bisperoxide 7 was used together with acid, and this combination also allowed polymerization at08C, which is significantly below the T 10h t1=2 of 7 (see Scheme 5above).…”
Section: Peroxide Initiatorsmentioning
confidence: 99%